External factors as mediators of work-life balance for generation Z - Hendratmoko Hendratmoko; Elisabeth Vita Mutiarawati; Heri Prabowo (Jurnal Ekonomi Perusahaan, 2025)
The contemporary landscape of human resource management has witnessed work-life balance (WLB) emerging as a critical strategic concern, particularly for Generation Z employees entering today's evolving work environment. The progression of digitalization, increasing productivity expectations, and individual aspirations for well-being have intensified the relevance of examining WLB. This study investigates how technological and psychological dimensions influence WLB and explores the mediating function of external factors in that relationship. Employing a quantitative methodology anchored in Structural Equation Modeling with Partial Least Squares (SEM-PLS) analysis, complemented by qualitative insights drawn from Gen Z employees' workplace experiences across various Indonesian firms. The findings reveal that psychological variables exert the strongest impact on WLB, both directly and through external mediating factors. In contrast, technological aspects have a limited direct effect and show insignificant mediation. The novelty of this study lies in conceptualizing external conditions such as social support networks and adaptive organizational culture as intermediaries connecting technological and psychological influences on WLB, a perspective rarely explored among Indonesia's younger workforce. The results highlight the importance of psychosocial-oriented strategies in addressing WLB challenges amid the digital era.